A review and assessment of Copernicus water quality and temperature products in coastal waters: insights from the Adriatic Sea - Milad Niroumand-Jadidi; Lorenzo Mentaschi; Francesco Riminucci; Simone Toller; Sonia Silvestri (Frontiers in Marine Science, 2026)
Several satellite-derived water quality and sea surface temperature (SST) products from the Copernicus program are available for coastal environments, but most rely on empirical algorithms that do not fully capture the bio-optical complexity of these waters. Unlike open-ocean conditions, coastal optical properties are shaped not only by chlorophyll-a (Chl-a) but also by total suspended matter (TSM) and colored dissolved organic matter (CDOM), whose variable contributions increase spectral complexity and challenge biophysical parameter retrieval. Consequently, the accuracy and reliability of Copernicus products in coastal zones remain insufficiently assessed and require further investigation. Here, we review and assess Copernicus products for the Northern Adriatic Sea (NAS). Multi-year in-situ measurements from optical and physical sensors are employed to evaluate the quality of satellite-derived products as well as those from biogeochemical models. The accuracy assessment is conducted using several performance metrics, including the coefficient of determination (R²) and the normalized root mean square error (NRMSE). In addition, we propose a bias-correction approach valid for the NAS to further improve the agreement between Copernicus products and in-situ coastal observations. The results show that SST products, whether satellite- or model-based, are highly reliable (NRMSE ≈ 3%). Various Chl-a products also demonstrate promising performance, particularly after bias correction (NRMSE< 10%). In contrast, the turbidity product exhibits reduced reliability, especially for values exceeding 4 FNU. Model-derived Chl-a and salinity products show substantial uncertainties. This study underscores the importance of appropriate bias-correction strategies to ensure the suitability of Copernicus products in optically complex coastal waters.

The Italian effort toward a coordinated observation of Essential Variables (EOV, ECV, EBV) in European Marine Environments. Long-term observation in the central Mediterranean seas and Italian coasts - Simone Toller; Emilio Urbinati; Debora Bellafiore; Caterina Bergami; Francesca De Pascalis; Marcello G. Magaldi; Marco Bellacicco; Federico Bellati; Maristella Berta; Angelo Boccacci; Roberto Bozzano; Fabio Brunetti; et al. (Frontiers in Marine Science, 2026)
Monitoring Essential Ocean, Climate, and Biodiversity Variables (EOVs, ECVs and EBVs) collected through the marine Research Infrastructures (RIs) is critical for assessing environmental status, improving scientific knowledge and defining environmental policies. This study evaluates the capacity of the Italian marine monitoring system, including facilities such as fixed stations, buoys, autonomous platforms, and mobile systems across the Mediterranean Sea, to produce those variables. Conducted in 2023 within the framework of the ITINERIS project ( https://itineris.cnr.it/ ), which aims to strengthen coordination among national and ESFRI RIs (European Strategy Forum on Research Infrastructures), the analysis systematically examines the spatial, thematic, and technological coverage of EOVs, ECVs, EBVs observations and their alignment with international standards for environmental monitoring of 155 facilities from eight Italian and pan-European marine RIs. Of the 107 EVs recognized, 50% were actively produced by the RIs considered, with over 90% meeting the established requirements for EVs. These numbers will be updated to reflect the new equipment acquired during the project’s implementation up to early 2026, which is expected to boost EVs production by approximately 38-40%. The national monitoring network demonstrates a high degree of maturity for oceanic and climate variables, while biodiversity observations remain less represented, indicating the need for further technological innovation and automation. These findings emphasize the importance of enhancing coordination and harmonization among RIs to ensure balanced and interoperable monitoring. The study provides key recommendations to strengthen Italy’s capacity to contribute to the global characterization of EOVs, ECVs, and EBVs and to support evidence-based environmental assessments and the development of robust environmental management strategies at European level.

Decadal analysis of chlorophyll fluorescence, algal blooms and driving factors from a fixed-point observing system in the Northern Adriatic Sea - Simone Toller; Francesco Riminucci; Emanuele Böhm; Lucilla Capotondi; Annamaria Correggiari; Chiara Lapucci; Emanuele Organelli; Mariangela Ravaioli; Rosalia Santoleri; Giuseppe Stanghellini; Caterina Bergami (Estuarine, Coastal and Shelf Science, 2025)

New insights into the migration, distribution and accumulation of micro-plastic in marine environment: A critical mechanism review - Javed Nawab; Haris Khan; Junaid Ghani; Mazhar Iqbal Zafar; Sardar Khan; Simone Toller; Laraib Fatima; Amir Hamza (Chemosphere, 2023)

Urban mining of municipal solid waste incineration (MSWI) residues with emphasis on bioleaching technologies: a critical review - Valerio Funari; Simone Toller; Laura Vitale; Rafael M. Santos; Helena I. Gomes (Environmental Science and Pollution Research, 2023)